Layout Design for a Low Capacity Manufacturing Line: A Case Study. (13th August 2013) - De Carlo, Filippo; Arleo, Maria Antonietta; Borgia, Orlando; Tucci, Mario
The layout re-arrangement of fashion production lines realizing many small batches is rarely deployed according to well-known engineering procedures. In fact, it would often appear too complex to call a plant engineer for the proper layout design of such small production lines. Rather, it is preferred to apply empirical methodologies when considering, generally, factory know-how, general business needs, safety requirements, and so on. In the present work, the results of a fashion manufacturing line re-layout were compared by analysing the current situation with the solutions provided by a "homemade" company design, both through a systematic layout planning approach and a broader lean reengineering activity. In order to evaluate the effectiveness of each solution, the different alternatives were compared with the help of a discrete event simulator, analysing productivity, transportation times and costs. The result of the case study showed a slight advantage with the lean approach in considering such efficiency indicators. In addition, the lean production methods allowed the designers to identify some inefficiencies that other approaches could not see, since the latter did not focus on production in a holistic way.